The Role of Mindfulness Practices in Mitigating Academic Stress: Implications for Student success in Higher Education - Lehloka, Motlatsi Cletus (Journal of Ecohumanism, 2025)
Higher education students often experience considerable academic pressure, which can substantially affect their mental health and academic performance. Supporting mental health while working to improve academic achievement is a challenging task for universities. This study examines the impact of academic stress and the use of mindfulness practices on university students’ academic performance. Mindfulness serves as a mechanism to reduce extraneous cognitive burden, thereby enhancing learning and performance while alleviating the effects of stress. This study systematically examines existing literature studies to explore the role of mindfulness practices in mitigation on students’ overall well-being and academic outcomes. The paper delves more into students’ well-being in higher education settings, exploring the methodologies, interventions strategies engaged and reported effects. Studies indicate that the integration of mindfulness techniques in educational settings enhances students’ mental health, emotional control, and stress alleviation. Furthermore, the tactics have the capacity to cultivate a constructive classroom atmosphere, strengthen interpersonal relationships, and augment overall student involvement. This study enhances comprehension of mindfulness meditation’s potential as an effective instrument for promoting students’ mental health and academic achievement. It emphasizes the significance of incorporating mindfulness techniques into school environments to promote comprehensive well-being.